Karakterisasi Morfologi dan Optimasi Kultur In Vitro Aksesi Ubi Jalar Daging Ungu (Ipomoea batatas L. Poiret) - Sabda, Muhamad; Margareth, Clarencia (Buitenzorg: Journal of Tropical Science, 2025)
Purple-fleshed sweet potato (Ipomoea batatas L. Poiret) is a functional food crop known for its high anthocyanin content and nutritional value. This study aimed to characterize the morphological traits of stem and leaf organs from seven purple-fleshed sweet potato accessions and to evaluate the effectiveness of in vitro culture techniques for their conservation. Morphological traits were assessed using a standardized scoring system and analyzed using Principal Component Analysis (PCA) and cluster analysis. Results showed significant variation among accessions, with Ungu Lonjong appearing genetically distinct, while Ayamurasaki, KT Lampa, and Local NTT exhibited high similarity. In vitro culture analysis involved the sterilization and cultivation of explants on Murashige and Skoog (MS) medium and minimal growth medium. The highest sterilization success rate was observed in Ungu Lonjong (78.3%), whereas Local NTT showed the highest contamination. This study demonstrates the potential of combining morphological data and tissue culture for effective characterization, conservation, and future purple-fleshed sweet potato germplasm breeding.   Keywords: Ipomoea batatas, germplasm conservation, morphological characterization, tissue culture